Inner Workings of a Cinchona Alkaloid Catalyzed Oxa‐Michael Cyclization: Evidence for a Concerted Hydrogen‐Bond‐Network Mechanism1. Issue 7 (4th January 2013) - Hintermann, Lukas; Ackerstaff, Jens; Boeck, Florian
Abstract Cinchona alkaloids catalyze the oxa‐Michael cyclization of 4‐(2‐hydroxyphenyl)‐2‐butenoates to benzo‐2, 3‐dihydrofuran‐2‐yl acetates and related substrates in up to 99 % yield and 91 % ee (ee=enantiomeric excess). Catalyst and substrate variation studies reveal an important role of the alkaloid hydroxy group in the reaction mechanism, but not in the sense of a hydrogen‐bonding activation of the carbonyl group of the substrate as assumed by the Hiemstra–Wynberg mechanism of bifunctional catalysis. Deuterium labeling at C‐2 of the substrate shows that addition of ROH to the alkenoate occurs with syn diastereoselectivity of ≥99:1, suggesting a mechanism‐based specificity. A concerted hydrogen‐bond network mechanism is proposed, in which the alkaloid hydroxy group acts as a general acid in the protonation of the α‐carbanionic center of the product enolate. The importance of concerted hydrogen‐bond network mechanisms in organocatalytic reactions is discussed. The relative stereochemistry of protonation is proposed as analytical tool for detecting concerted addition mechanisms, as opposed to ionic 1, 4‐additions.